Development And Validation Of Derivative Spectroscopic Method For Simultaneous Estimation Of Cefixime Trihydrate And Azithromycin Dihydrate In Combined Dosage Form - VISHAL SHAH,; DR. HASUMATI RAJ, (International Journal of Pharma and Bio Sciences, 2012)
A novel, simple, accurate, sensitive, reproducible, economical spectroscopic method was developed and validated for the determination of Azithromycin dihydrate and Cefixime trihydrate in combined dosage form. Second order derivative spectroscopy method is adopted to eliminate spectral interference. The method obeys Beer’s Law in concentration ranges of 10-40 ppm for Cefixime trihydrate and 25-100 ppm of Azithromycin dihydrate. The method was validated for linearity, accuracy and precision as per ICH guidelines. The zero crossing point for Azithromycin dihydrate and Cefixime trihydrate was 328 nm and 231.6 nm, respectively in water. The LOD and LOQ value were found to be 0.13 and 0.38 ppm for Cefixime trihydrate and 0.80 and 2.44 ppm for Azithromycin dihydrate respectively. The developed and validated method was successfully used for the quantitative analysis of commercially available dosage form (ZIMNIC -AZ).